2018
DOI: 10.1002/cjce.23141
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous ozone decomposition over high silica zeolitic frameworks

Abstract: For several decades, it has been known that ozone emissions are harmful to humans, plants, and animals. Heterogeneous catalytic decomposition is an efficient process for removing ozone from air. This study examines the effect of the zeolite's framework and pore width on efficiency for decomposing gaseous ozone. Four highly hydrophobic zeolites are used: a large cavity zeolite (Faujasite/H-FAU), a medium pore zeolite with parallel channel (Mordenite/H-MOR), and two medium pore zeolites with interconnected chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
3
3
0
Order By: Relevance
“…100ZSM‐5 x‐y and 200ZSM‐5 x‐y showed three bands at 1440, 1490 and 1550 cm −1 for Lewis, Lewis+Brønsted and Brønsted acid site respectively. The band for Lewis acid appeared at a comparatively lower wavelength (1440 cm −1 ) which can be attributed to the presence of two types of Lewis acid site; one could be attributed to the presences of extra framework alumina or electronic defaults in the framework alumina [24,25] . This observation is in agreement with those proposed by Marques et al [26] .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…100ZSM‐5 x‐y and 200ZSM‐5 x‐y showed three bands at 1440, 1490 and 1550 cm −1 for Lewis, Lewis+Brønsted and Brønsted acid site respectively. The band for Lewis acid appeared at a comparatively lower wavelength (1440 cm −1 ) which can be attributed to the presence of two types of Lewis acid site; one could be attributed to the presences of extra framework alumina or electronic defaults in the framework alumina [24,25] . This observation is in agreement with those proposed by Marques et al [26] .…”
Section: Resultssupporting
confidence: 91%
“…This observation is in agreement with those proposed by Marques et al [26] . for Beta zeolite and Nicolas Brodu et al [24] . for ZSM‐5 zeolite.…”
Section: Resultsmentioning
confidence: 99%
“…IR evidence obtained here suggests that a surface reaction occurs between adsorbed toluene at Brønsted acid sites and active oxygen species generated after ozone adsorption and decomposition at Lewis acid sites. Such a surface reaction mechanism is in agreement with previous reports, that claim the adsorption of toluene molecules at Brønsted acid sites and the adsorption of ozone molecules at Lewis acid sites followed by its transformation into active oxygen species [32,48,[55][56][57]. After that, it has been indicated that active oxygen species interact with adsorbed toluene molecules, leading to the formation of toluene oxidation by-products, as reported elsewhere [58,59].…”
Section: Ftir Evidence Of the Heterogeneous Catalytic Ozonation Of To...supporting
confidence: 92%
“…This type of degradation leads to the formation of adsorbed oxygenated species such as atomic oxygen, peroxide ions and hydroxyl radicals as described in a mechanism proposed by Li et al [141]. The use of ozone over a catalytic surface therefore produces a great variety of species from molecular gases to short lifetime radicals, which are available for coke oxidation [142,143]. The following set of equations describes ozone decomposition over metal oxides and zeolites.…”
Section: Ozonationmentioning
confidence: 99%